Nutrition and food aid -- different modalities, different impacts: lessons from Ethiopia - Quisumbing, Agnes R. (International Food Policy Research Institute, 2003)
Both food for work and free distributiona are reaching poor and vulnerable households ahd have a positive direct impact on weight-for-height. The benefits of the programmes vary depending on the sex of the child, and at times, the sex of the recipient.